Gender Performativity in Children Picture Books Introducing Teddy and Julian is A Mermaid - Sunardi Sunardi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the interpretation of the issue of gender performativity in the two picture books, Introducing Teddy (2016) and Julian Is A Mermaid (2018), written by Jessica Walton and Jessica Love. From the data analysis, it was found that these two picture books portray how gender performativity exists in society. Identification of social construction is also discussed in these two picture books. The persumption of the binary system is that women should align with her gender that is feminine, while men should be masculine. This process is called gender performativity of gender which was asserted by Judith Butler theory. The result of this research reveals that the gender performativity and gender construction in the two picture books surrounded all aspects of human life. The society constructed color, appearance, traits, acts, gestures, roles, and stereotypes based on individuals’ gender category. It is also found that the characters from the two picture books were gender fluid with certain stages conforming to the performativity but also to the gender construction.